An Approach for Synthesis of Modulated M-Channel FIR Filter Banks Utilizing the Frequency-Response Masking Technique. (28th November 2006) - Rosenbaum Rosenbaum, Linnéa Linnéa; Löwenborg Löwenborg, Per Per; Johansson Johansson, Håkan Håkan
Abstract : The frequency-response masking (FRM) technique was introduced as a means of generating linear-phase FIR filters with narrow transition band and low arithmetic complexity. This paper proposes an approach for synthesizing modulated maximally decimated FIR filter banks (FBs) utilizing the FRM technique. A new tailored class of FRM filters is introduced and used for synthesizing nonlinear-phase analysis and synthesis filters. Each of the analysis and synthesis FBs is realized with the aid of only three subfilters, one cosine-modulation block, and one sine-modulation block. The overall FB is a near-perfect reconstruction (NPR) FB which in this case means that the distortion function has a linear-phase response but small magnitude errors. Small aliasing errors are also introduced by the FB. However, by allowing these small errors (that can be made arbitrarily small), the arithmetic complexity can be reduced. Compared to conventional cosine-modulated FBs, the proposed ones lower significantly the overall arithmetic complexity at the expense of a slightly increased overall FB delay in applications requiring narrow transition bands. Compared to other proposals that also combine cosine-modulated FBs with the FRM technique, the arithmetic complexity can typically be reduced by40 % in specifications with narrow transition bands. Finally, a general design procedure is given for the proposed FBs and examples are included to illustrate their benefits.